Akuntansi Syariah dalam Implementasi Sistem Informasi Akuntansi pada e-Commerce di Indonesia - Laila, Ahrina; Lidyah, Rika (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
This study aims to analyze the implementation of sharia accounting in supporting the development of civil society through sharia-based economic activities. The methodology of this study uses qualitative research, through literature studies, regulatory documentation, and studies of several case studies on e-commerce platforms in Indonesia that have implemented sharia principles. The data collection technique in this study uses book journal literature, while the analysis used is descriptive analysis. The results of the study show that the importance of a good sharia accounting information system in E-Commerce is to be a filter in transactions, so that a quality E-Commerce ecosystem will be created in terms of service and transactions. The application of an accounting information system in E-Commerce is considered necessary to be a basis for business actors and consumers in making transactions so that mistakes do not occur.